2017
DOI: 10.1039/c7cc03095a
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of polypeptides containing the unnatural amino acid 2-aminoisobutyric acid

Abstract: Polypeptides containing 2-aminoisobutyric acid (Aib) units as an unnatural amino acid residue were synthesized by papain-catalyzed chemoenzymatic polymerization of a tripeptide ethyl ester l-Ala-Aib-l-Ala-OEt in an aqueous medium. The Aib-containing polypeptide adopted an α-helix conformation in both the solid and solution phases, which was induced by the periodic Aib residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 38 publications
1
49
0
Order By: Relevance
“…Chemoenzymatic synthesis of polypeptides containing aromatic residues Unnatural amino acids are generally unfavorable substrates for chemoenzymatic polymerization using proteases due to their substrate specificity. Indeed, no polymer was obtained for the papain-catalyzed polymerization of the aromatic amino acid monomer 4-aminobenzoic acid ethyl ester (Abz-OEt), resulting in approximately complete recovery of the monomer, as observed in the case of other unnatural amino acids such as 2-aminoisobutyric acid and nylon esters (Scheme 1) [21,27]. To overcome the poor specificity of the Abz unit to papain, we modified the Abz unit with Gly or Ala at both termini to obtain tripeptide ethyl esters via a solution-based condensation method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemoenzymatic synthesis of polypeptides containing aromatic residues Unnatural amino acids are generally unfavorable substrates for chemoenzymatic polymerization using proteases due to their substrate specificity. Indeed, no polymer was obtained for the papain-catalyzed polymerization of the aromatic amino acid monomer 4-aminobenzoic acid ethyl ester (Abz-OEt), resulting in approximately complete recovery of the monomer, as observed in the case of other unnatural amino acids such as 2-aminoisobutyric acid and nylon esters (Scheme 1) [21,27]. To overcome the poor specificity of the Abz unit to papain, we modified the Abz unit with Gly or Ala at both termini to obtain tripeptide ethyl esters via a solution-based condensation method.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that the poor affinity of unnatural amino acids to proteases can be mitigated by modification with natural amino acids in chemoenzymatic polymerization. A tripeptide ester consisting of 2-aminoisobutyric acid (Aib) between two alanine residues was efficiently polymerized in the presence of papain, whereas the chemoenzymatic polymerization of Aib ester did not proceed because of low affinity to papain [27,28]. The resulting polypeptide with an Aib-containing periodic sequence transitioned to an α-helix secondary structure, driven by the helix-inducing Aib units.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl [79] Alkaline d-peptidase (2-4) [79] Aib b) Ethyl [123] Papain (4-5) [123] 3-Aminopropionic acid Methyl, [73,124] ethyl [73,124] Papain (6-9) [73,124] 4-Aminobutyric acid Methyl, [73,124] ethyl [73,124] Papain (5-9) [73,124] 6-Aminohexanoic acid Methyl [73,124] Papain (6-9) [73,124] a) Values in parentheses show the range of average degree of polymerization (DP) obtained using the proteases; b) Polymerization was conducted using a tripeptide ester containing an Aib unit.…”
Section: Materials and General Protocolsmentioning
confidence: 99%
“…Aib-containing polypeptides were enzymatically synthesized by utilizing a tripeptide ester containing an Aib unit in the middle of the triad sequence. [123] Sandwiching the Aib unit with l-alanine residues, which are good substrates for papain, resulted in the efficient recognition of the substrate by papain and allowed the polymerization of the tripeptide ester to proceed. The resulting polypeptide, poly(AlaAibAla), assumed a helical conformation in both solid and solution states, as confirmed by IR and circular dichroism analyses.…”
Section: Introduction Of Unnatural Structures Into Polypeptide Backbonesmentioning
confidence: 99%
See 1 more Smart Citation